2018
DOI: 10.1161/atvbaha.117.310126
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Aortic Aneurysms Growth Is Associated With High Concentrations of Plasma Proteins in the Intraluminal Thrombus and Diseased Arterial Tissue

Abstract: Objective-Porosity of the intraluminal thrombus (ILT) is believed to convey biologically active components from the bloodstream toward the aneurismal wall. Accumulation of molecules in the abdominal aortic aneurysmatic tissue may influence vascular protein turnover and regulate abdominal aortic aneurysm growth. We sought to identify proteins with concentrations in the ILT and the abdominal aortic aneurysm wall which associate with aneurysmal expansion rate. Approach and Results-Proteomic analysis by liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Arresten and Canstatin (degradation products of COL4A1 and -A2, respectively) have anti-angiogenic activity 7 , but whether these peptides play a significant role in AAA pathogenesis remains elusive. Recently, AXT107—a peptide derived from sequences of both COL4A1 and COL4A5 58 was proposed as a drug displaying strong anti-permeability effects on several vessel types 58 , 59 —an effect which could also be relevant in the context of AAA 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Arresten and Canstatin (degradation products of COL4A1 and -A2, respectively) have anti-angiogenic activity 7 , but whether these peptides play a significant role in AAA pathogenesis remains elusive. Recently, AXT107—a peptide derived from sequences of both COL4A1 and COL4A5 58 was proposed as a drug displaying strong anti-permeability effects on several vessel types 58 , 59 —an effect which could also be relevant in the context of AAA 60 .…”
Section: Discussionmentioning
confidence: 99%
“…137 Correspondingly, proteomic analysis showed that TRX protein in the human AAA wall sample is negatively correlates with the growth rate, which is in line with hypothesis that upregulation of TRX in defense against ROS may slow down the aneurysm expansion rate. 138 A similar dependency of TAA on increased ROS has been observed, as in vitro and ex vivo studies on human TAA tissue revealed that oxidative stress mediates VSMC phenotypic switching towards synthetic phenotype through connective tissue growth factor. 139 These results was further validated in a mouse model of TAA which showed similar pathology as observed in human tissue.…”
Section: Oxidative Stresssupporting
confidence: 53%
“…It should be mentioned that the mediators from plasma and those produced by ILT-trapped neutrophils were observed both in the thrombus and in adjacent aneurysm walls. Additionally, one study has shown that canaliculi, through which cells and proteins travel, are also present in abluminal layers of ILT and the AAA walls and are even larger than those in luminal layers, which could allow both larger molecules and cells to reach the wall [ 53 , 54 ]. The presence of such a leaky ILT and a spongy vessel wall that can allow proteases and other unfavourable molecules to accumulate and degrade components of the wall could ultimately lead to AAA diameter widening and subsequent rupture.…”
Section: Discussionmentioning
confidence: 99%